A drill-integrated miniaturized device for detecting ice in lunar regolith: the PROSPECT permittivity sensor. (29th September 2021) - Trautner, R; Reiss, P; Kargl, G
Abstract: The detection and characterization of lunar resources, including water ice, is a key area of interest for a new generation of lunar missions. The electrical properties of water ice in the extremely low frequency range support its detection by means of in-situ permittivity measurements. A new type of miniaturized subsurface permittivity sensor is presented, which is under development for the PROSPECT package on the Luna-27 lander mission. Here, the sensor concept is described, key design features are presented and possible operations modes are introduced. The expected accuracy for measurements of the relative permittivity along the borehole is ∼10–15% and depends mainly on the accuracy of borehole geometry models. Laboratory test results from a prototype sensor on a water ice/simulant mixture at cryogenic temperatures are presented, demonstrating the capability to detect water ice at 125 K. The improved capabilities of the flight design are discussed, operational modes are explained and alternative electrode configurations for lunar landers and rovers are proposed.